Formação de Professores em Materiais Manipulativos no contexto da Lesson Study com vistas a uma Alfabetização Matemática Inclusiva - Silva, Davi Cezar da (2023)
Teaching and learning mathematics in kindergarten and early grades of elementary schools has generated discussions in the literature regarding the challenges faced by teachers. Adding to such challenges is the policy of inclusion. Among the possible responses to promote inclusive education, as a focus for this study, is the development and adaptation of manipulative materials in mathematics classes. In this context and the insertions of new content knowledge, the use of those materials can be characterized as tools that aim at teaching all students, characterizing an inclusive mathematical literacy. In this research, we investigate the aspects of a lesson planning, based on the Lesson Study methodology, in the stages of development or direction, adaptation and application of manipulative materials for an Inclusive Mathematical Literacy, in a continuing education of teachers. The research was based on the question: what aspects of a teacher professional learning about using manipulative materials in the context of Lesson Study for inclusive mathematical literacy contributed (or not) to teacher learning? To answer the question, we describe the networks and categories that emerged from the narratives of the participating teachers, highlighting teachers' learning throughout the Lesson Study. To meet the general objective, based on under the qualitative action research, using observations and interventions, we proposed and evaluated possibilities related to mathematics teaching practices. Through implementation, we proposed a workflow based on the Lesson Study cycle, generating a systematization for the elaboration, direction, adaptation, and application of inclusive manipulative materials. As a result, we understand that when group work is collaborative, it optimizes and strengthens proposals that aim to promote inclusive education. In this sense, the extension course contributed to the professional learning of the participants. We verified that the proposed workflow stimulated reflections about teachers’ practices, indicating possible future changes for the participating teachers. The Lesson Study also promoted the construction of new knowledge both in relation to the documents that guide the schools and in specific issues of mathematics. Thus, we hope that this research contributes to teacher professional development and learning and, consequently, to the learning and inclusion of students, as well as to expand the possibilities in relation to manipulative materials for an inclusive mathematical literacy.